2016
DOI: 10.1155/2016/2974521
|View full text |Cite|
|
Sign up to set email alerts
|

The Motivating Function of Healthcare Professional in eHealth and mHealth Interventions for Type 2 Diabetes Patients and the Mediating Role of Patient Engagement

Abstract: eHealth and mHealth interventions for type 2 diabetes are emerging as useful strategies to accomplish the goal of a high functioning integrated care system. However, mHealth and eHealth interventions in order to be successful need the clear endorsement from the healthcare professionals. This cross-sectional study included a sample of 93 Italian-speaking type 2 diabetes patients and demonstrated the role of the perceived ability of healthcare professionals to motivate patients' initiative in improving the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 68 publications
6
43
0
3
Order By: Relevance
“…Such initiatives are also essential to ensure the professional well-being of nurses themselves by valuing and recognizing their crucial role in addressing the challenges of the current healthcare environment. If demonstrated effective, learning programs teaching clinicians how to use and act on patient engagement measures in clinical practice might be a key steps in supporting the realization of patient engagement in healthcare (Barello et al, 2015a; Graffigna et al, 2016). Researchers and clinicians from different clinical areas should collaborate to share good practices and develop guidelines to advance the field of patient engagement and shift from theory into practice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such initiatives are also essential to ensure the professional well-being of nurses themselves by valuing and recognizing their crucial role in addressing the challenges of the current healthcare environment. If demonstrated effective, learning programs teaching clinicians how to use and act on patient engagement measures in clinical practice might be a key steps in supporting the realization of patient engagement in healthcare (Barello et al, 2015a; Graffigna et al, 2016). Researchers and clinicians from different clinical areas should collaborate to share good practices and develop guidelines to advance the field of patient engagement and shift from theory into practice.…”
Section: Resultsmentioning
confidence: 99%
“…From this perspective, previous studies have demonstrated a positive correlation between the patients' perception of their clinicians' support for autonomy in self-care and the patients' level of engagement in self-management behaviors and adherence to treatments (Graffigna et al, 2016). There are also studies that discussed the role of health practitioners' beliefs about the importance of patients being active agents in managing their health condition (Greene and Yedidia, 2005; Blakeman et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These include self-efficacy, personality traits, different coping capacities, various dimensions of stress, and social support, as well as the relationship between the patient and health care professionals 9. Patient adherence appeared to be directly influenced by the perceived level of health care professionals ability to motivate patients’ autonomy 10. Family support is another issue that can influence self-management, a study done in 17 countries showed the experiences of family members who support adults living with diabetes: worries about hypoglycemia, employment, how the diabetes negatively affects the relationship and the help of the family member to make positive life changes for their health 11,12…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been suggested that PCC increases patient outcomes and satisfaction in chronic illnesses [45,46] and type 2 diabetes [47]. Thus, using the Web for medical and health facts is an approach in healthcare that can support empowerment and is facilitated by a shift to PCC that can subsequently improve selfmanagement [25,30,48,49] 50] to provide alternatives to them apart from the primary health care centres, and this gives a certain degree of freedom [51]. However, a benefit for healthcare professionals using digitalised technology in selfmanagement support is the option to be in contact with patients more frequently than semi-annually or annually, as is common today [52].…”
Section: Discussionmentioning
confidence: 99%